Instinct - Smith, George O. (George Oliver), 1911-1981; Martinez (Salt Lake City, UT : Project Gutenberg, 2007)
"Instinct" by George O. Smith is a science fiction novella penned in the late 1950s. The story revolves around the themes of communication, human nature, and the cyclical rise and fall of civilizations, specifically reflecting on the interactions between humans from Earth (referred to as Terra) and a more advanced alien race. The narrative explores the difficulties that arise when different species attempt to understand each other's motivations and behaviors. The plot centers on Jerry Markham, a Terran astronaut, who is captured by an alien race after landing on a foreign planet. The aliens, led by Chelan, are intrigued but perplexed by the Terrans' propensity for conflict and their relentless drive to push boundaries despite past failures. As Markham finds himself isolated from communication and subjected to experimental isolation to uncover the secrets of human instinct, he begins to reflect deeply on memory and communication. Ultimately, the aliens learn that despite shutting off his sensory inputs, the essence of Markham's being$1 (Bthe drive to connect and communicate$1 (Bremains unyielding, prompting a recognition of humanity$1 (Bs persistent will to thrive, even when faced with adversity. The story concludes with the aliens reconsidering their approach to humanity, acknowledging its resilience and intrinsic nature. (This is an automatically generated summary.)s
Release date is 2007-12-20
Greg Weeks, Bruce Albrecht, Stephen Blundell and the Online Distributed Proofreading Team
Keywords: Science fiction; Short stories